ECONOMIC DETERMINANTS OF INNOVATIVE DECISIONS IN THE GLOBAL DENTAL SERVICES MARKET (INNOVATIVE ECONOMY, 2025)
Stakhanskyy O.O. ECONOMIC DETERMINANTS OF INNOVATIVE DECISIONS IN THE GLOBAL DENTAL SERVICES MARKETPurpose. The aim of the article is to substantiate the key economic determinants influencing innovative solutions in the dental services market, and to evaluate of major innovations in dental practice.Methodology of research. The study used general scientific and special methods, which ensured a comprehensive approach to identifying the economic determinants of innovative development in the global dental services market. The work applies methods of theoretical generalization – to substantiate the role of economic factors in supporting innovation in the global market for dental services; economic analysis, synthesis – to examine key economic determinants and group them, and to systematize major innovations in dentistry; content analysis of international reports and industry reviews – to identify the main trends in the development of the dental services market and in the adoption of innovations; a comparative approach – to determine the advantages of the principal innovations in the market; and SWOT analysis toolkit – to synthesize the strengths, weaknesses, opportunities, and threats associated with implementing innovations in Ukraine’s dental services market.  Findings. The impact of digital technologies on the transformation of the global dental services market was confirmed, and groups of economic determinants for innovative decision-making were identified. It was confirmed that modern challenges significantly hinder the introduction of innovations, which requires the adoption of appropriate strategies, which were substantiated by the author. The main innovations in the global dental services market were systematized, the degree of their implementation in Ukraine and worldwide was determined, and the main advantages have identified. The significance of such an innovation as Digital Smile Design was substantiated. The peculiarities of introducing innovative products into the activities of dental clinics in Ukraine were revealed. A SWOT analysis of the implementation of innovative solutions in the Ukrainian dental services market was conducted. Promising directions for the innovative development of the dental services market were formulated. Originality. Further development was given to research substantiating the role of economic determinants in making innovative decisions in the global and national dental services markets. Key economic determinants are identified and grouped; major innovations in dentistry are systematized; based on the results of SWOT analysis, the potential and threats of implementing innovative solutions in the Ukrainian dental services market are identified.Practical value. The obtained results and drawn conclusions can be used in formulating strategies for introducing innovations in dental clinics, developing state programs to support digital dentistry, and assessing the prospects for the development of the dental services market. Key words: dental services, global dental services market, innovations, economic determinants, digital transformation, digital technologies, artificial intelligence, Digital Smile Design.
Keywords: dental services; global dental services market; innovations; economic determinants; digital transformation; digital technologies; artificial intelligence; Digital Smile Design